EFEK MODERASI KEPEMILIKAN MANAJERIAL TERHADAP HUBUNGAN LIKUIDITAS, PROFITABILITAS DAN LEVERAGE DENGAN NILAI PERUSAHAAN - Muthia Harnida; Siti Mardah; Netty Nurhayati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This research aims at examining and analyzing the effect of liquidity (current ratio), profitability (return on assets), and leverage (debt to equity ratio) on company value with the proxy of Tobin’s Q. This study also investigates the moderation effect of managerial ownership on the relationship among liquidity, profitability, and leverage on company value. The sample of this research is manufacturing companies of consumer goods with 74 observations for the period of 2015 to 2021. The result using the multiple regression analysis and moderated regression analysis shows that profitability has a significant effect on the company value, but liquidity and leverage have no significant effect on the company value. The moderation effect of managerial ownership affects the relationship between liquidity and the company value. Meanwhile, managerial ownership cannot moderate the relationship between profitability (return on asset) and leverage (debt to equity ratio) on the company value.